2003
DOI: 10.1111/j.1708-8208.2003.tb00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading of Brånemark System® TiUnite™ and Machined‐Surface Implants in the Posterior Mandible: A Randomized Open‐Ended Clinical Trial

Abstract: The present study demonstrated a 10% higher success rate following immediate loading of partial fixed bridges in the posterior mandible supported by TiUnite surface implants compared with success with machined implants. When using the machined implants, the number of failed implants was significantly higher in smokers and in bone quality 4 sites. Such findings were not seen following the use of TiUnite implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
191
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(216 citation statements)
references
References 5 publications
18
191
0
7
Order By: Relevance
“…The reverse torque removal values are directly related to the contact bone/ implant interface, bone density, quantity of cortical bone around the torque after certain periods. There was no significant differences between the torques induced by machined and anodized surfaces of test groups in the present experiment, which is in agreement with others reports [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Likewise, no difference was observed in the control groups.…”
Section: ■ Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The reverse torque removal values are directly related to the contact bone/ implant interface, bone density, quantity of cortical bone around the torque after certain periods. There was no significant differences between the torques induced by machined and anodized surfaces of test groups in the present experiment, which is in agreement with others reports [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Likewise, no difference was observed in the control groups.…”
Section: ■ Discussionsupporting
confidence: 83%
“…According to Zhu et al 10 modified surfaces improve biocompatibility, increase cellular adhesion and proliferation. Studies by Rocci et al 5 and Bahat 11 have indicated that modifications of the surface and macro design of the implant are particularly important for its longevity.…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation
“…Surfaces on TiUnite®, TiXos® and sand-blasted implants are three typical types of implant surfaces that were investigated in this work. The fact that these implants can promote osseointegration at different levels has already been an indisputable fact [14][15][16]26,27]. By using conventional evaluation methods, e.g., histomorphometrical evaluations, removal torque tests, and success and failure criteria, a series of parameters such as BIC, removal torque and implant survival rate can be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sample prepared by argon ion beam cross section polishing is not suitable for TEM observation, it fits well for SEM observation to reveal the bone formation mechanisms. Furthermore, the functional mechanism of the surfaces of TiUnite®, TiXos® and sand-blasted implants during osseointegration can be elucidated, which is different from the other clinical evaluation or comparative trial of the implants with turn machined surface [14][15][16].…”
Section: Introductionmentioning
confidence: 99%